Radiological risk assessment and characteristics of 210Po in selected water sources in Quang Nam and Da Nang, Vietnam - Hao Duong, Van-; Chu Trung, Tien; Danh Tran, Hung; Nguyen Thi, Oanh; Do Xuan, Duc; Ha Nguyen Thi, Hoang; Dinh Viet, Hung (Vietnam Journal of Earth Sciences, 2023)
210Po, one of the harmful natural isotopes with a long enough half-life, plays a significant role in environmental processes. 48 samples, including groundwater (dug wells, thermal water, and drill wells) and surface water (lakes, rivers, and streams) in the Da Nang - Quang Nam region of Vietnam were analyzed by an alpha spectrometer. Relatively low activities of 210Po have been observed, whose mean values ranged from 0.15 to 4.58 and 1.34 mBq.L-1. There is no significant variation in 210Po activities between groundwater and surface water groups. The average 210Po activity of those groups is 1.28 and 1.40 mBq.L-1, respectively. The geological conditions of the study area, neutral pH values, and predominant oxidizing conditions supported the low 210Po activities in the selected water sources. Average annual effective doses for adults, children, and infants due to the consumption of water containing 210Po were found to be 1.15, 1.21, and 2.94 µSv.y-1, respectively.